NEGATIVE INFLUENCE OF DEBRIS FLOWS ON THE FUNCTIONING OF NATURAL AND INDUSTRIAL SYSTEMS AND EVALUATION OF DEBRIS FLOW HAZARD OF TRIBUTARY STREAMS OF DIFFERENT ORDER WITHIN MOKRYANKA AND BRUSTURIANKA RIVER BASIN - Shevchuk, V.; Ivanik, O.; Tsybulska, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main types of debris flows negative influence on the functioning of natural and industrial systems were identified and analyzed. Geological and geomorphological structure of Mokryanka and Brusturianka river basins was characterized. The model results of debris flowsʼ dynamic effects on engineering construction were reviewed. The Algorithm and created on its basis a software module "Mudflows", which was used for the calculations, were outlined. The influence of soil moisture and flux density on the hydrodynamic force and total pressure were analyzed.